Facing Human Capital Challenges of the 21st Century Education and Labor Market Initiatives in Lebanon, Oman, Qatar, and the United Arab Emirates - Gonzalez, Gabriella C. (RAND Corporation, 2008)
Describes the education and labor market initiatives implemented or under way in four countries in the Arab region--Lebanon, Oman, Qatar, and the United Arab Emirates--to address the human resource issues they each face as they prepare their countries for a place in the 21st century global economy. Together, these countries highlight the variety of challenges faced by countries in the region and responses to those challenges.